(untitled) (Web of Teachers: Inderscience Research, 2025)
The article analyzes the importance and production of organizing general astronomy according to modular teaching methods. The modular educational process, its development processes, and support in the educational process are highlighted. The specific laboratory conditions that should be considered when organizing education based on software are discussed, as well as the role of students’ preparatory skills and didactic materials. The article extensively discusses the impact of modular education on the independent acquisition of students’ knowledge, the democratization of the educational process, and the improvement of efficiency.